Zinc-based metal organic framework material as well as preparation method and application thereof

Through the adoption of zinc-based metal organic framework materials, the unique mesh channel structure is used to solve the problems of high energy consumption and limited adsorbent selectivity in traditional separation processes, and the efficient separation of propane and ethane is achieved, which improves propane/ The separation properties of ethane, propane/methane and propylene/ethylene are suitable for industrial applications.

CN119285974AActive Publication Date: 2025-01-10BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411410907.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

In traditional separation processes, low-temperature distillation and adsorption separation technologies have problems with high energy consumption and limited selectivity of adsorbents. It is difficult to efficiently separate propane and ethane in natural gas, affecting the quality of methane and the acquisition of other high-value-added chemical products.

Method used

The zinc-based metal organic framework material is used. This material forms a hybrid coordination frame of pcu topology through N and O coordination, forming an interconnected mesh channel, increasing the adsorption site of C3 hydrocarbons and improving the separation performance of low-carbon hydrocarbons. The material is formed by self-assembly of zinc ions and 1H-indazole-5-carboxylic acid by coordination. The preparation method includes mixing a dilute solution of zinc salt and organic ligand, reacting and purification treatment, forming a high-quality large particle single Crystal material.

Benefits of technology

It has achieved efficient adsorption of propane and propylene, enhancing the adsorption selectivity of propane/ethane, propane/methane and propylene/ethylene, and the separation efficiency can reach 100%. It is suitable for industrial applications, and has a simple process, is cheap and easy to obtain, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285974A_ABST
    Figure CN119285974A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-based metal organic framework material as well as a preparation method and application thereof. The zinc-based metal organic framework material comprises a mixed coordination framework which is formed by coordination of N and O and has pcu topology, and the minimum asymmetric unit of the zinc-based metal organic framework material is composed of three zinc ions, three deprotonated 1H-indazole-5-carboxylic acids and bridging water molecules. The preparation method comprises the following steps: heating a zinc salt aqueous solution to a reaction temperature, keeping for 30-40 minutes, cooling, and filtering for later use; dissolving an organic ligand in an organic solvent to obtain a ligand solution, heating to a reaction temperature, keeping for 30-40 minutes, and filtering for later use; mixing the standby solutions obtained by respective filtration, removing impurities, and adding a regulator to obtain a mixed solution; and carrying out standing reaction and purification treatment. The zinc-based metal organic framework material provided by the invention is a porous material formed by coordination self-assembly of an organic ligand and zinc ions, has a large specific surface area and aromatic ring modified pore walls, is more beneficial to adsorption of propylene and propane and weakening of adsorption of other low-carbon hydrocarbons, and is high in separation selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of separation materials for mixed gases, and in particular relates to a zinc-based metal organic framework material and a preparation method and application thereof. Background Art

[0002] Since the 21st century, the total amount of global CO2 emissions has continued to increase, and global extreme climate phenomena have frequently occurred. Natural gas (mainly methane) is a type of clean fossil energy that can replace oil, with the characteristics of high efficiency and low CO2 emissions. On the other hand, the use of methane as a raw material to prepare high-value-added chemicals has attracted much attention and is of great significance for its comprehensive application in the chemical industry. Therefore, it is necessary to separate high-purity methane from natural gas. In addition to methane, natural gas also contains propane and ethane, the presence of which reduces the energy density and utilization efficiency of natural gas. At the same time, propane and ethane are also important raw materials for the preparation of other high-value-added petrochemical products. Efficient separation of natural gas and recovery of propane and ethane from it can not only improve the quality of methane, but also obtain high-value propane and ethane, which is a job that kills two birds with one stone.

[0003] The MTO process, which converts natural gas into synthesis gas and then converts the synthesis gas into low-carbon olefins through methanol, can produce chemical products propylene and ethylene. Propylene and ethylene are important raw materials for the synthesis of polypropylene and polyethylene and have important commercial value. Therefore, it is of great significance to efficiently and thoroughly separate the propylene and ethylene obtained in the MTO process to obtain polymerization-grade individual products.

[0004] So far, the traditional separation process still uses cryogenic distillation for separation, which is energy-intensive. The traditional adsorbents in the pressure swing adsorption process for adsorption separation of C1 / C2 / C3 still have certain limitations in terms of adsorption capacity and selectivity.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a zinc-based metal organic framework material and a preparation method and application thereof to solve the above problems.

[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0008] The present invention provides a zinc-based metal organic framework material, which comprises a mixed coordination framework with pcu topology formed by simultaneous N and O coordination, wherein the minimum asymmetric unit is composed of three zinc ions, three deprotonated 1H-indazole-5-carboxylic acids and bridging water molecules.

[0009] Three zinc ions coordinate with water molecules and the N element in 1H-indazole-5-carboxylic acid to form a trinuclear zinc cluster, and the O element in 1H-indazole-5-carboxylic acid further coordinates with zinc to form a six-connected Zn3N6O7 cluster. The clusters are connected by deprotonated 1H-indazole-5-carboxylic acid to form interconnected mesh channels. The formed mesh channels can provide more adsorption sites for C3 hydrocarbons, thereby increasing the adsorption amount of C3 hydrocarbons and having good separation performance for low-carbon hydrocarbons.

[0010] The present invention also provides a method for preparing the zinc-based metal organic framework material, comprising the following steps:

[0011] S1: heating the zinc salt aqueous solution to the reaction temperature and maintaining it for 30-40 minutes, then cooling, filtering and setting aside;

[0012] S2: dissolving an organic ligand in an organic solvent to obtain a ligand solution, then heating to a reaction temperature and maintaining the temperature for 30-40 minutes, filtering, and setting aside; the organic ligand comprises 1H-indazole-5-carboxylic acid and / or a 1H-indazole-5-carboxylic acid derivative;

[0013] The structural formula of the 1H-indazole-5-carboxylic acid is:

[0014]

[0015] Since the organic ligand 1H-indazole-5-carboxylic acid contains two coordination elements, N and O, according to the hard-soft acid-base theory, the metal ion of its coordination center can be Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ 、Mo 2+ , Tc 2+ 、In 3+ , Pb 2+ 、Bi 3+ , but the preferred coordinating metal is zinc because it can form 6-connected Zn3N6O7 clusters and thus construct a three-dimensional framework of pcu topology.

[0016] Therefore, the zinc salt includes any one or more of zinc nitrate, zinc sulfate, zinc acetate, zinc formate, zinc chloride, zinc bromide, zinc perchlorate, zinc phosphate, zinc acetylacetonate, zinc trifluoromethanesulfonate, and zinc oxalate; considering that different metal salts have different solubility in solvents, zinc nitrate with better solubility is preferred;

[0017] Preferably, the concentration of the zinc salt aqueous solution is 0.1 to 0.5 mol L -1 ; A further preferred concentration is 0.3 molL -1;

[0018] The organic solvent includes any one or more of N,N-diethylformamide, N,N-dimethylacetamide, and N,N-dimethylformamide;

[0019] Preferably, the concentration of the ligand solution is 0.01 to 0.1 mol L -1 ; A further preferred concentration is 0.025 molL -1 ;

[0020] S3: The standby solutions obtained by filtering S1 and S2 respectively are mixed and impurities are removed, and then a regulator is added to obtain a mixed solution; the regulator includes any one or more of nitric acid, hydrochloric acid, sulfuric acid, formic acid, and acetic acid; the regulator is an acid, and the acid used should correspond to the anion of the zinc salt used. For example, zinc nitrate is used as the zinc salt, and nitric acid is used as the regulator, and so on, to promote the dissolution of the reactants and better react to form grid channels.

[0021] Preferably, the volume ratio of the zinc salt aqueous solution to the ligand solution is 1-10:1-10; in order to improve the crystallinity of the metal organic framework material during the static reaction and obtain larger particles of the metal organic framework material, the volume ratio of the zinc salt aqueous solution to the ligand solution is further preferably 1:4.

[0022] S4: The mixed solution obtained in S3 is allowed to stand for reaction, and the reaction product is purified to obtain the zinc-based metal organic framework material. The temperature of the standing reaction, i.e., the reaction temperature described in S1 and S2, is 60 to 140° C., and the reaction time is 1 to 7 days, so as to form a long-range ordered three-dimensional network channel structure.

[0023] The purification treatment comprises: soaking the reaction product in solvent I for three days, replacing solvent I at least three times a day, so as to dissolve and remove unreacted raw materials; then soaking the product in solvent II for three days, replacing solvent II at least three times a day, so as to replace solvent I with a high boiling point in the pores; and finally performing vacuum activation;

[0024] The solvent I includes any one of N,N-diethylformamide, N,N-dimethylacetamide, N,N-dimethylformamide or water, preferably N,N-dimethylformamide;

[0025] The solvent II is any one of methanol, ethanol, acetone, dichloromethane, chloroform or tetrahydrofuran, preferably methanol;

[0026] The temperature of the vacuum activation is 25-60° C., and the time is 1-24 hours.

[0027] The purpose of preparing the zinc salt and the organic ligand into a dilute solution with a low concentration and then mixing them is to, on the one hand, create a dilute solution environment, which is conducive to the gradual crystallization of the metal organic framework material in the process of growing into a single crystal, forming long-range ordered channels, and reducing the generation of defects, which will affect the adsorption and separation performance of the material; on the other hand, it reduces the coordination rate of the metal ion and the organic ligand. If the rate is too fast, precipitation will form, making it difficult to form the three-dimensional network conversion channel. According to the concentration and rate set by the present invention, a high-quality, large-particle single-crystal granular metal organic framework material can be formed, which can better exert the actual adsorption potential of the material.

[0028] At the same time, the dilute solutions of zinc salt aqueous solution and organic ligand solution are heated to the reaction temperature and then filtered, so as to remove the precipitates produced in each process, so as to reduce the generation of impurities as much as possible, improve the purity of the product, and at the same time reduce the negative impact of impurities on the formation of large-grained metal organic framework material single crystals, thereby further promoting the formation of high-quality, large-grained single crystals.

[0029] The present invention also provides an application of the zinc-based metal organic framework material, which is used for separating low-carbon hydrocarbon mixed gas at a separation temperature of -50 to 100° C. and a pressure of 0 to 1 bar.

[0030] When the zinc-based metal organic framework material provided by the present invention is used to adsorb and separate propane in a propane-containing mixed gas, the propane-containing mixed gas includes: a mixed gas of propane and ethane, a mixed gas of propane and methane, or a mixed gas of propane, ethane and methane;

[0031] Optionally, in the mixed gas of propane and ethane, the volume ratio of propane to ethane is 1:99-99:1; in the mixed gas of propane and methane, the volume ratio of propane to methane is 1:99-99:1; or, in the mixed gas of propane, ethane and methane, the volume ratio of propane, ethane and methane is 5:10:85;

[0032] When used for adsorbing and separating propylene in a propylene / ethylene mixed gas, the volume ratio of propylene to ethylene in the propylene and ethylene mixed gas is 1:99 to 99:1.

[0033] Beneficial effects of the present invention:

[0034] The invention provides a novel metal organic framework material, which is a porous material formed by coordination self-assembly of an organic ligand 1H-indazole-5-carboxylic acid or its derivatives and zinc ions, and has a large specific surface area and pore walls modified with aromatic rings.

[0035] The preparation method provided by the invention has cheap and readily available raw materials, simple process, mild reaction conditions and is suitable for large-scale production.

[0036] The metal organic framework material provided by the present invention has a simple preparation and purification process, extremely low degassing requirements, is applicable to a wider range of operating conditions such as temperature and pressure, is easy to industrially apply, and has a unique structure that allows it to adsorb more propylene and propane, and weakens the adsorption of methane, ethane and ethylene. While increasing the adsorption amount of propane and propylene, the adsorption selectivity of propane / ethane, propane / methane and propylene / ethylene is enhanced, and it has a good propane / ethane, propane / methane and propylene / ethylene gas mixture separation potential, and the separation efficiency can reach 100%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a physical appearance picture of the zinc-based metal organic framework material crystal provided in Example 1;

[0039] Figure 2 A structural diagram of a zinc-based metal organic framework material crystal provided in Example 1;

[0040] Figure 3 The single component adsorption curves of propane, ethane and methane measured at 273K for the zinc-based metal organic framework material provided in Example 1;

[0041] Figure 4 The single component adsorption curves of propane, ethane and methane measured at 298K for the zinc-based metal organic framework material provided in Example 1;

[0042] Figure 5 Calculation diagram of adsorption heat of propane, ethane and methane for the zinc-based metal organic framework material provided in Example 1;

[0043] Figure 6 The IAST selectivity calculation diagram of the zinc-based metal organic framework material provided in Example 1 for propane, ethane and methane;

[0044] Figure 7 The single component adsorption curve of propylene and ethylene measured at 273K for the zinc-based metal organic framework material provided in Example 1;

[0045] Figure 8The single component adsorption curve of propylene and ethylene measured at 298K for the zinc-based metal organic framework material provided in Example 1;

[0046] Fig. 9 The calculation diagram of the adsorption heat of propylene and ethylene of the zinc-based metal organic framework material provided in Example 1;

[0047] Fig.10 The IAST selectivity calculation diagram of the zinc-based metal organic framework material provided in Example 1 for propylene and ethylene;

[0048] Fig.11 (a) is a physical appearance picture of the zinc-based metal organic framework material crystal provided in Example 2;

[0049] Fig.11 (b) is a physical appearance picture of the zinc-based metal organic framework material crystal provided in Comparative Example 1;

[0050] Fig.11 (c) is the appearance of the product provided in Comparative Example 2;

[0051] Fig.11 (d) is an appearance diagram of the product provided in Comparative Example 6;

[0052] Fig.11 (e) is the appearance of the product provided in Comparative Example 7. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] This embodiment provides a zinc-based metal organic framework material, and the preparation method thereof comprises the following steps:

[0056] S1: Dissolve 9 g zinc nitrate hexahydrate in 100 mL deionized water, sonicate to dissolve the solid completely, seal the reaction bottle, heat it in a constant temperature oven to 100 °C for 30 minutes, cool it to room temperature, and filter to obtain 0.3 mol L -1 of aqueous zinc nitrate;

[0057] S2: Dissolve 2.8 g of 1H-indazole-5-carboxylic acid in 1000 mL of N,N-diethylformamide, sonicate to dissolve the solid completely, seal the reaction bottle, heat to 100 °C for 30 minutes, cool to room temperature, and filter to obtain 0.025 mol L -1 1H-indazole-5-carboxylic acid solution;

[0058] S3: Add 1 mL of 0.3 mol L-1 zinc nitrate aqueous solution prepared in S1 and 4 mL of 0.025 mol L-1 zinc nitrate aqueous solution prepared in S2 to a 20 mL sample bottle. -1 1H-indazole-5-carboxylic acid solution was mixed by ultrasound, filtered and then 0.125 mL of concentrated nitric acid was added to obtain a colorless and transparent mixed solution;

[0059] S4: The colorless and transparent mixed solution obtained in S3 was sealed, placed in a constant temperature oven at 100°C for 5 days, filtered and the crystals were collected, and the crystals were first washed with solvent N'N-diethylformamide for three days, with fresh solvents replaced three times a day, and then washed with solvent methanol for three days, with fresh solvents replaced three times a day; and then vacuum dried for 12 hours to obtain purified and dried [Zn3(C8H4N2O2)3·H2O] n The crystals were vacuum activated at 60° C. for 12 hours on an activation station of an adsorption instrument to obtain the zinc-based metal organic framework material provided in this embodiment.

[0060] The physical appearance of the zinc-based metal organic framework material crystal prepared in this embodiment is as follows: Figure 1 As shown by Figure 1 It can be seen that the zinc-based metal organic framework material prepared in this embodiment has larger crystal particles and better crystal morphology.

[0061] The crystal structure diagram of the zinc-based metal organic framework material prepared in this embodiment is shown in Figure 2 As shown by Figure 2 It can be seen that the zinc-based metal organic framework provided in this embodiment is a mixed coordination framework with pcu topology formed by the simultaneous presence of N and O coordination. It can be seen from the single crystal structure analysis that its minimum asymmetric unit is composed of three zinc ions, three deprotonated 1H-indazole-5-carboxylic acids and bridging water molecules. Three zinc ions coordinate with water molecules and the N element in 1H-indazole-5-carboxylic acid to form a trinuclear zinc cluster, and further the O element in 1H-indazole-5-carboxylic acid coordinates with zinc to form a six-connected Zn3N6O7 cluster, and the clusters are connected by deprotonated 1H-indazole-5-carboxylic acid to form an interconnected mesh channel. The mesh channel formed in this way can provide more adsorption sites for C3 hydrocarbons, thereby increasing the adsorption amount of C3 hydrocarbons, and has good separation performance for low-carbon hydrocarbons.

[0062] Take 100 mg of the activated product sample and measure the single component adsorption curves of propane, ethane and methane at 273K. The results are as follows: Figure 3 As shown, the single component adsorption curves of propane, ethane and methane were measured at 298K. The results are as follows Figure 4 As shown. Figure 3-4 It can be seen that the adsorption trend of the material provided in this embodiment for the three gases propane, ethane and methane is propane>ethane>methane.

[0063] Figure 5 The adsorption heat of propane, ethane and methane for the material provided in this embodiment is calculated by fitting the single component adsorption curves of propane, ethane and methane at 273K and 298K using the Ville equation. Figure 5 It can be seen that the order of adsorption heat of the material for propane, ethane and methane is Qst(propane)>Qst(ethane)>Qst(methane), indicating that the material has a strong interaction with propane, making it have a larger propane adsorption capacity.

[0064] Figure 6 The IAST selectivity is calculated by fitting the single-component adsorption curves of propane, ethane, and methane of the material provided in this embodiment at 298K with a two-point Langmuir equation. Figure 6 It can be seen that it has high propane / ethane and propane / methane selectivity, indicating that the material has very strong propane / ethane and propane / methane selective separation performance.

[0065] Take 100 mg of the activated product sample and measure the single component adsorption curves of propylene and ethylene at 273K. The results are as follows: Figure 7 As shown, the single component adsorption curves of propylene and ethylene were measured at 298K. The results are as follows Figure 8 As shown. Figure 7-8 It can be seen that the adsorption trend of the material provided in this embodiment for the two gases propane, ethane and methane is propylene>ethylene.

[0066] Fig. 9 The adsorption heat of propylene and ethylene is calculated by fitting the single component adsorption curves of propylene and ethylene of the material provided in this embodiment at 273K and 298K using the Ville equation. Fig. 9 It can be seen that the order of adsorption heat of propylene and ethylene of the material is Qst(propylene)>Qst(ethylene), which shows that the material has a strong interaction with propylene, making it have a larger propylene adsorption capacity.

[0067] Fig.10 The IAST selectivity is calculated by fitting the single component adsorption curves of propylene and ethylene of the material provided in this embodiment at 298K with a two-point Langmuir equation. Fig.10 It can be seen that it has a very high propylene / ethylene selectivity, indicating that the material has a very strong propylene / ethylene selective separation performance.

[0068] Example 2

[0069] The difference from Example 1 is that the zinc salt used in S1 is zinc chloride, and correspondingly, the regulator used in S3 is hydrochloric acid.

[0070] The physical appearance of the zinc-based metal organic framework material crystal prepared in this embodiment is as follows: Fig.11 As shown in (a), Fig.11 (a) It can be seen that the zinc-based metal organic framework material crystal was successfully prepared in this embodiment, and the appearance is acceptable; Fig.11 (a) with Figure 1 It can be seen from the comparison that the morphology of the crystal particles in this example is slightly worse than that of the crystals obtained using zinc nitrate in Example 1.

[0071] Comparative Example 1

[0072] The only difference from Example 1 is that S1 dissolves 9 g of zinc nitrate hexahydrate in 100 mL of deionized water and filters to obtain 0.3 mol L -1 The zinc nitrate aqueous solution is then directly involved in the subsequent reaction without being subjected to a temperature-raising and static treatment.

[0073] The obtained product crystal particles are very small, such as Fig.11 (b) as shown.

[0074] Comparative Example 2

[0075] The only difference from Example 1 is that S2 is to dissolve 2.8 g of 1H-indazole-5-carboxylic acid in 1000 mL of N,N-diethylformamide, dissolve the solid completely by ultrasonication, and filter to obtain 0.025 mol L -1 The 1H-indazole-5-carboxylic acid solution is directly used in the subsequent reaction without being heated and allowed to stand.

[0076] The crystal particles of the obtained product are too small. Fig.11 As shown in (c), the expected effect cannot be achieved.

[0077] Comparative Example 3

[0078] The only difference from Example 1 is that no concentrated nitric acid is added after filtration in step S3.

[0079] Results: No MOF crystals were obtained during the reaction cycle.

[0080] Comparative Example 4

[0081] The only difference from Example 1 is that the regulator added after filtration in step S3 is hydrochloric acid.

[0082] Results: No MOF crystals were obtained during the reaction cycle.

[0083] Comparative Example 5

[0084] The only difference from Example 1 is that the regulator added after filtration in step S3 is sulfuric acid.

[0085] Results: No MOF crystals were obtained during the reaction cycle.

[0086] Comparative Example 6

[0087] The only difference from Example 1 is that in step S1, 90 g of zinc nitrate hexahydrate is dissolved in 100 mL of deionized water, and the solid is completely dissolved by ultrasound. The reaction bottle is sealed and placed in a constant temperature oven, heated to 100° C. for 30 minutes, and then filtered after cooling to room temperature to obtain 3 mol L -1 of aqueous zinc nitrate.

[0088] Results: No metal organic framework crystals were obtained during the reaction cycle. Fig.11 As shown in (d), this is because the salt solution concentration is too high, resulting in a too fast reaction rate and failure to form a crystalline structure.

[0089] Comparative Example 7

[0090] The only difference from Example 1 is that in step S2, 28 g of 1H-indazole-5-carboxylic acid is dissolved in 1000 mL of N,N-diethylformamide, and the solid is completely dissolved by ultrasound. The reaction bottle is sealed and heated to 100° C. for 30 minutes. After cooling to room temperature, the mixture is filtered to obtain 0.25 mol L -1 of 1H-indazole-5-carboxylic acid solution.

[0091] Results: No metal organic framework crystals were obtained during the reaction cycle. Fig.11 As shown in (e), this is because the ligand concentration is too high, resulting in low polymerization degree during the coordination reaction, making it difficult to generate a crystalline structure for precipitation.

[0092] The zinc-based metal organic framework material provided by the present invention has high propane and propylene adsorption performance, has the potential to separate propane from propane / ethane and propane / methane mixed gases, has the potential to separate ethane from ethane / methane, and has the potential to adsorb propane and ethane from propane / ethane / methane mixed gases and purify methane. At the same time, the zinc-based metal organic framework material can also be used to separate propylene from propylene / ethylene mixed gases.

[0093] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A zinc-based metal organic framework material, characterized in that: The zinc-based metal organic framework material includes a mixed coordination framework with pcu topology formed by simultaneous N and O coordination, and its minimum asymmetric unit is composed of three zinc ions, three deprotonated 1H-indazole-5-carboxylic acids and bridging water molecules.

2. A method for preparing a zinc-based metal organic framework material as claimed in claim 1, characterized in that: The following steps are involved: S1: heating the zinc salt aqueous solution to the reaction temperature and maintaining it for 30-40 minutes, then cooling, filtering and setting aside; S2: dissolving the organic ligand in an organic solvent to obtain a ligand solution, then heating to a reaction temperature and maintaining the temperature for 30-40 minutes, filtering and setting aside; S3: The standby solutions obtained by filtering S1 and S2 are mixed and impurities are removed, and then a regulator is added to obtain a mixed solution; S4: allowing the mixed solution obtained in S3 to stand for reaction, and purifying the reaction product to obtain the zinc-based metal organic framework material.

3. The preparation method according to claim 2, characterized in that: The zinc salt includes any one or more of zinc nitrate, zinc sulfate, zinc acetate, zinc formate, zinc chloride, zinc bromide, zinc perchlorate, zinc phosphate, zinc acetylacetonate, zinc trifluoromethanesulfonate, and zinc oxalate; Preferably, the concentration of the zinc salt aqueous solution is 0.1 to 0.5 mol L -1 .

4. The preparation method according to claim 2, characterized in that: The organic ligand includes 1H-indazole-5-carboxylic acid and / or 1H-indazole-5-carboxylic acid derivatives; The structural formula of the 1H-indazole-5-carboxylic acid is: The organic solvent includes any one or more of N,N-diethylformamide, N,N-dimethylacetamide, and N,N-dimethylformamide.

5. The preparation method according to claim 2 or 4, characterized in that: The concentration of the ligand solution is 0.01 to 0.1 mol L -1 .

6. The preparation method according to claim 2, characterized in that: The volume ratio of the zinc salt aqueous solution to the ligand solution is 1-10:1-10.

7. The preparation method according to claim 2, characterized in that: The regulator includes any one or more of nitric acid, hydrochloric acid, sulfuric acid, formic acid and acetic acid.

8. The preparation method according to claim 2, characterized in that: The temperature of the static reaction, i.e. the reaction temperature described in S1 and S2, is 60 to 140° C., and the reaction time is 1 to 7 days.

9. The preparation method according to claim 2, characterized in that: The purification treatment comprises: soaking the reaction product in solvent I for three days, replacing solvent I at least three times a day, so as to dissolve and remove unreacted raw materials; then soaking the product in solvent II for three days, replacing solvent II at least three times a day, so as to replace solvent I with a high boiling point in the pores; and finally performing vacuum activation; The solvent I includes any one of N,N-diethylformamide, N,N-dimethylacetamide, N,N-dimethylformamide or water; The solvent II is any one of methanol, ethanol, acetone, dichloromethane, chloroform or tetrahydrofuran; The temperature of the vacuum activation is 25-60° C., and the time is 1-24 hours.

10. A use of the zinc-based metal organic framework material as claimed in claim 1, characterized in that: Used for separation of low-carbon hydrocarbon mixed gases, the separation temperature is -50 to 100°C and the pressure is 0 to 1 bar.

Citation Information

Patent Citations

  • Preparation and selective adsorption application of zinc-based metal organic framework material

    CN113603897A

  • Yttrium-based metal organic framework material as well as preparation method and application thereof

    CN113769715A

  • Zinc-based metal organic framework material, preparation method thereof and application of zinc-based metal organic framework material in ethylene separation

    CN116082657A

  • Metal organic framework material as well as preparation method and application thereof

    CN117696012A

  • Water stable zinc-based metal organic framework and method of use

    US20200190114A1

Cited By

  • Method for constructing energetic transition metal complex based on waste biomass cellulose as well as product and application of energetic transition metal complex

    CN120714703A